Effectiveness of Moringa oleifera extract supplementation in increasing Glucagon-like peptide-1 (GLP-1) in prediabetic model - Rusminingsih, Esri; Susanto, Hardhono; Afifah, Diana Nur; Wibowo, Judiono; Anas, Yance (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2024)
Prediabetes is a serious global health problem. The prevalence of prediabetes is estimated to be higher than that of diabetes mellitus (DM), and 5%-12.5% of prediabetic patients will develop DM. Epidemiological studies showed that consumption of polyphenol-rich foods impacts blood glucose control and improves insulin resistance. Moringa leaves contain high levels of flavonoids that are effective in glucose control. This study aimed to determine the effect of moringa leaf extract supplementation on increasing GLP-1 levels in prediabetes models. This study used a randomized controlled trial-post-test-only design. Twenty-five male Rattus norvegicus were divided into five groups, namely the normal group, the prediabetes group, and three intervention groups, each given moringa leaf extract at a dose of 75 mg/kgbb, 150 mg / kgbb and 225 mg / kgbb. After 4 weeks of intervention, a GLP-1 examination was conducted. Data analysis using the ANOVA test. There was a significant difference in GLP-1 levels in the intervention group compared to the prediabetes control group (p<0.05). GLP-1 levels increased as the dose given increased. In the intervention group, the dose of 225 mg/kg bw showed the highest increase in GLP-1 levels, but there was no significant difference compared to the 150 mg/kg bw dose group. Moringa leaf extract supplementation is proven to increase GLP-1 in the Rattus norvegicus model. The effect gets better with increasing doses. Further development and testing related to this supplementation are needed so it can be used as a safe non-pharmacological treatment for prediabetes and DM patients.